2021
DOI: 10.1016/j.celrep.2021.109637
|View full text |Cite
|
Sign up to set email alerts
|

Acute SARS-CoV-2 infection is associated with an increased abundance of bacterial pathogens, including Pseudomonas aeruginosa in the nose

Abstract: Highlights d Acute SARS-CoV-2 infection is associated with shifts in the nasal microbiome d Abundance of Pseudomonas aeruginosa increases with SARS-CoV-2 viral RNA load d Healthcare providers and infected patients share some nasal microbiome features d The nasal transcriptome of infected patients reveals inflammation and neuron damage

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 85 publications
(71 reference statements)
7
52
2
Order By: Relevance
“…Our alpha diversity observations contrast with two previous studies [11,12] that found a decrease in alpha diversity among SARS-CoV-2 infected specimens; however, these studies did not account for disease severity. We found significant differences in beta diversity among our study groups, consistent with other groups that have found significant beta diversity clustering between SARS-CoV-2-infected and uninfected subjects [9,10,11]. However, we did see significant overlap in the confidence ellipses, suggesting that although significant, the magnitude of compositional differences in the microbiota among our study groups are relatively small.…”
Section: Discussionsupporting
confidence: 90%
“…Our alpha diversity observations contrast with two previous studies [11,12] that found a decrease in alpha diversity among SARS-CoV-2 infected specimens; however, these studies did not account for disease severity. We found significant differences in beta diversity among our study groups, consistent with other groups that have found significant beta diversity clustering between SARS-CoV-2-infected and uninfected subjects [9,10,11]. However, we did see significant overlap in the confidence ellipses, suggesting that although significant, the magnitude of compositional differences in the microbiota among our study groups are relatively small.…”
Section: Discussionsupporting
confidence: 90%
“…Three of them, Severe Acute Respiratory Syndrome coronavirus (SARS-CoV), Middle East Respiratory Syndrome coronavirus (MERS-CoV), and Severe Acute Respiratory Syndrome coronavirus 2 (SARS-CoV-2), belonging to the Betacoronavirus genus, can cause severe infections that can lead to deaths [ 2 ]. Like the other human coronaviruses, SARS-CoV-2 is mainly transmitted through the upper respiratory tract by aerosolized droplets carrying viral particles [ 3 ], binding to the angiotensin-converting enzyme 2 ACE-2 receptor, whose expression is particularly high in the nasal and oral cavity cells [ 4 , 5 ]. Generally, COVID-19 patients show a wide clinical picture after 2–14 days post-viral exposure, ranging from absence of clinical manifestation, presence of mild symptoms, such as cold, fatigue, nausea, and fever to more severe symptoms, such as respiratory distress and pneumonia [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the nasal microbiome has been observed to be altered in several respiratory infections including COVID-19 affecting the course of the disease and clinical outcome ( 44 ). Different metagenomic studies portrayed decrease in the nasopharyngeal microbiome diversity in SARS-CoV-2 infected patients, leading to predominance of a specific microbe that correlated with symptom severity ( 22 , 23 , 45 ).…”
Section: Discussionmentioning
confidence: 99%